2013
DOI: 10.1093/mnras/stt2279
|View full text |Cite
|
Sign up to set email alerts
|

Effects of baryon removal on the structure of dwarf spheroidal galaxies

Abstract: Dwarf spheroidal galaxies (dSphs) are extremely gas-poor, dark matter-dominated galaxies, which make them ideal to test the predictions of the cold dark matter (CDM) model. We argue that the removal of the baryonic component from gas-rich dwarf irregular galaxies, the progenitors of dSphs, can substantially reduce their central density. Thus, it may play an important role in alleviating one of the problems of the CDM model related to the structure of relatively massive satellite galaxies of the Milky Way (MW).… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
105
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(107 citation statements)
references
References 116 publications
(138 reference statements)
2
105
0
Order By: Relevance
“…D.1. Similar to Arraki et al (2014), the removal of baryons in NBF-50 produces a dramatic loss in dark matter density (and therefore mass within the 1 kpc and 3 kpc boundaries), although the mass loss is slightly under that found by Arraki et al possibly attributable to the instantaneous removal of the baryons here. The tidal model NTO-50 retains the central mass density of NRPS-50, and tracks it closely until the first perigalacticon.…”
Section: D1 Mass Evolutionsupporting
confidence: 72%
See 1 more Smart Citation
“…D.1. Similar to Arraki et al (2014), the removal of baryons in NBF-50 produces a dramatic loss in dark matter density (and therefore mass within the 1 kpc and 3 kpc boundaries), although the mass loss is slightly under that found by Arraki et al possibly attributable to the instantaneous removal of the baryons here. The tidal model NTO-50 retains the central mass density of NRPS-50, and tracks it closely until the first perigalacticon.…”
Section: D1 Mass Evolutionsupporting
confidence: 72%
“…de Blok et al 2008;Walker & Peñarrubia 2011;Breddels & Helmi 2013) and, as the inner profile can alter the tidal evolution (Kazantzidis et al 2013), simulating the internal star formation is vitally important to understanding the evolution of a dwarf. In addition to the internal star formation changing its profile, the removal of gas also impacts the inner density (Arraki et al 2014) and the inclusion of this baryon loss may lead to a lower fraction of surviving dwarfs than expected from simulations that retain gas. In addition the metallicity evolution is intricately linked with the star formation history (and contributes towards its regulation through cooling), and with high-resolution studies of dwarf spheroidals now available (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, analyses of stellar subpopulations within several dSphs indicate cored central density profiles [4,[59][60][61][62] (except for Draco [63]). Several studies using hydrodynamical simulations have suggested that baryonic physics -i.e., feedback from star formation and supernovae, as well as ram pressure and tidal stripping from the host halo -may induce dSph cores [64][65][66][67], while Ref. [68] found a smaller impact from baryonic effects.…”
Section: Self-interacting Dark Matter and Small Scale Structurementioning
confidence: 95%
“…43) are consistent with this expectation, with density profile slopes that are negligibly affected by feedback at the 0.5-kpc scale. On the other hand, high-resolution simulations of luminous satellites in the halo of Milky Way-like hosts do show reduced central dark matter densities from a combination of early feedback effects with ram pressure stripping and tidal heating by the host halo and disk, processes that can extract energy from the host galaxy's gravitational potential (50)(51)(52). Alternatively, Kuhlen et al (53) argue that the regulation of star formation by molecular hydrogen cooling may make the stellar content of galaxies highly stochastic at a halo mass as high as 10 10 M ⊙ (also ref.…”
Section: Solutions In Baryonic Physics?mentioning
confidence: 99%